2016
DOI: 10.1007/s10971-016-4126-9
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel template preparation of alumina nanofillers for reinforcing the epoxy resin

Abstract: Alumina nanofibers were prepared by sol-gel template method. Carbon nanofibers (CNFs) of feather-like morphology obtained by chemical vapor deposition of C 2 -C 4 hydrocarbons mixture have been used as a template. The distinctive feature of CNF is a friable disordered structure consisting of separate fragments of graphite-like phase. To simplify the sol-gel synthetic procedure, the impact of preparative conditions such as type of precursor and ratio of starting components was studied. CNFs were coated with cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The performance of a composite dielectric can be significantly influenced by the incorporation of nanoparticles into epoxy resin, as indicated by several scientific studies. Alumina nanofibers were successfully synthesized via the sol-gel template method by Pavel V. Krivoshapkin et al, and incorporating them into epoxy composites led to significant enhancements in both thermal stability and mechanical strength properties [19]. Pan Hu et al successfully functionalized the surface of nano TiO2 by grafting a silane coupling agent, KH570, onto its hydroxyl groups, resulting in the preparation of an epoxy resin nanocomposite material.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of a composite dielectric can be significantly influenced by the incorporation of nanoparticles into epoxy resin, as indicated by several scientific studies. Alumina nanofibers were successfully synthesized via the sol-gel template method by Pavel V. Krivoshapkin et al, and incorporating them into epoxy composites led to significant enhancements in both thermal stability and mechanical strength properties [19]. Pan Hu et al successfully functionalized the surface of nano TiO2 by grafting a silane coupling agent, KH570, onto its hydroxyl groups, resulting in the preparation of an epoxy resin nanocomposite material.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the addition of fillers improves the tribological properties. Krivoshapkin et al [ 39 ] explored the reinforcing effect of alumina nanofibers on the epoxy matrix and found that, increase in mechanical strength of the epoxy composite filled with optimal content of 1% alumina nanofibers. Niaki el al.…”
Section: Introductionmentioning
confidence: 99%